2020
DOI: 10.3390/nano10122511
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapour Deposition of Graphene for Durable Anticorrosive Coating on Copper

Abstract: Due to the excellent chemical inertness, graphene can be used as an anti-corrosive coating to protect metal surfaces. Here, we report the growth of graphene by using a chemical vapour deposition (CVD) process with ethanol as a carbon source. Surface and structural characterisations of CVD grown films suggest the formation of double-layer graphene. Electrochemical impedance spectroscopy has been used to study the anticorrosion behaviour of the CVD grown graphene layer. The observed corrosion rate of 8.08 × 10−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…c Schematic of a common chemical vapor deposition setup for synthesis of graphene. Reprinted with permission from [ 61 ]. Copyright 2020 Multidisciplinary Digital Publishing Institute.…”
Section: Properties and Synthesis Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…c Schematic of a common chemical vapor deposition setup for synthesis of graphene. Reprinted with permission from [ 61 ]. Copyright 2020 Multidisciplinary Digital Publishing Institute.…”
Section: Properties and Synthesis Of Graphenementioning
confidence: 99%
“…In another study, graphene was deposited by CVD as a durable anticorrosive coating on copper using ethanol as a carbon source (Fig. 3c ) [ 61 ]. Methane (CH 4 ) was used as gas precursors to provide stable carbon flow at average growth temperature set around 1000 °C.…”
Section: Properties and Synthesis Of Graphenementioning
confidence: 99%
“…Therefore, modifying the graphene deposition technique for producing high quality, low defect graphene seems an essential step in this regard. In order to produce high-quality CVD-grown graphene, using ethanol as a gas precursor was suggested by Ji et al 71 A bi-layer graphene was produced on Cu substrate that reduced the corrosion rate of the substrate 24 times compared to the bare Cu. Moreover, the stability of the corrosion protection behaviour of the graphene coating was investigated by storing the coated sample for one year in the ambient environment, which indicated that the graphene coating could preserve its barrier properties over time.…”
Section: Graphene Coatings On Copper Nickel Platinum and Stainless Steelmentioning
confidence: 99%